1-Benzoyl-3-[(2-benzylsulfanyl)phenyl]thiourea - Bhattacharjee, Tirtha; Gogoi, Prasanta; Puranik, Vedavati G.; Gawade, Rupesh L.; Barman, Pranjit (Acta Crystallographica Section C-Crystal Structure Communications, 2012)
In the title compound, C21H18N2OS2, a strong intramolecular N-H center dot center dot center dot O hydrogen bond [N center dot center dot center dot O = 2.642 (3) angstrom] between the amide N atom and the benzoyl O atom forms an almost planar six-membered ring in the central part of the molecule. In the crystal, molecules are packed through weak N-H center dot center dot center dot S interactions. Intra- and intermolecular hydrogen bonds and van der Waals interactions are the stabilizing forces for the crystal structure.

Synthesis, characterization, and crystal structure determination of palladacycles of para-substituted 2-thiobenzylazobenzenes - Bhattacharjee, Tirtha; Kalita, Mukul; Chakravarty, Debamitra K.; Barman, Pranjit; Puranik, Vedavati G. (Journal of Coordination Chemistry, 2014)
Bichelated neutral palladacycles (1-3), [Pd(L)Cl], were synthesized from reaction of the new potential tridentate (C,N,S) ligands, 2-thiobenzylazobenzene (L-1), 4'-methyl-2-thiobenzylazobenzene (L-2), and 4'-chloro-2-thiobenzylazobenzene (L-3) with sodium tetrachloropalladate(II), Na-2[PdCl4], in ethanol. The compounds were characterized by elemental analysis, FT-IR, H-1 NMR, UV-visible, and thermogravimetric analysis. The crystal structures of L-2 and 1-3 were determined by single-crystal X-ray diffraction. In 1-3, the geometry around palladium remains almost square planar, coordinated to carbon, nitrogen, and sulfur of the ligand forming a bichelated cyclopalladate complex. The C-H center dot center dot center dot Cl type intermolecular hydrogen bonds, weak pi center dot center dot center dot pi, C-H center dot center dot center dot pi, and van der Waals interactions are believed to be the stabilizing forces for the crystal packing of these palladacycles.
Keywords: 2-Thiobenzylazobenzene; CNS-donor ligand; crystal structure; Palladacycles; Thermogravimetric analysis